Us against them : the political culture of talk radio - Bobbitt, Randy, 1955- (Lexington studies in political communication., 2010)
Why do people choose to listen to political talk instead of music on the radio? Randy Bobbitt addresses this and other crucial questions as he closely examines the phenomenon of talk radio and the role that it plays in the American political process and popular culture.--[book cover].